The Influence Of Problem-Based Learning Models On Mathematics Learning Outcomes For Grade IV SDN Kedungotok - Tita Yuliani; Emy Yunita Rahma Pratiwi (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2022)
The problem solving ability of students in mathematics is relatively low. It takes a learning model that can help students to solve problem solving in mathematics, which is a problem-based learning model or PBL. This study aims to determine the effect of the problem-based learning model on the learning outcomes of fourth grade students at SDN Kedungotok Tembelang Jombang. This research is quantitative with the type of experimental research design. The population is all fourth grade students, totaling 27 students, the sample taken consists of one class. Sampling was carried out using a non-probability sampling technique with total sampling type, this study was conducted in two meetings, the first meeting the students were given learning not using the PBL model, the next meeting the students were given learning using the PBL model. This research instrument is pre-test and post-test. Data analysis in this study used statistical analysis with the help of SPSS software. The results of the study concluded: (1) the ability to understand the material of circumference and area of ​​flat shapes before using the PBL model in fourth grade students of SDN Kedungotok Tembelang students obtained an average score of 49.33. (2) the ability to understand the material of perimeter and area of ​​flat shapes after using the PBL model in fourth grade students of SDN Kedungotok Tembelang obtained an average score of 89.56. (1) the effect of learning mathematics around and area of ​​flat shapes for fourth grade students of SDN Kedungotok shows that there is a significant effect of 0.000. The significant value shows 0.000 < 0.05 so that H0 is rejected and H1 is accepted. That is, this study has an effect on student learning outcomes and there is a significant effect between students' ability to understand the circumference and area of ​​the flat figure before and after using the PBL model. Keywords: Influence, learning outcomes, problem-based learning